A "forensic biobank" to establish comprehensive genetic frequency data for Switzerland. (May 2019) - Zieger, Martin; Utz, Silvia
Highlights: Experience from building a blood bank for population genetics is shared. For the first time, a subsample from the Italian speaking region is included. New comprehensive autosomal allele frequencies for Switzerland are presented. A concordance check between GlobalFiler ® and PowerPlex ® Fusion 6C is presented. The informative value of the three Y-STRs in the PowerPlex ® Fusion was assessed. Abstract: Comparatively little knowledge is available about the genetic structure of the Swiss population. Missing allele frequency data for some markers frequently used in forensics and paternity / kinship testing is just one practical aspect of this lack of genetic data. Therefore, in an attempt to fill this gap, we established a biobank of 1198 Swiss blood samples, systematically collected throughout the whole country. For the first time, this collection contains a population sample from the southernmost Italian speaking canton of Ticino. In this article, we share the experiences gained with the sampling procedure. Furthermore we present autosomal allele frequencies for 23 loci and a concordance check between the two multiplex PCR kits GlobalFiler ® and PowerPlex ® Fusion 6C. Statistical evaluation of the data revealed only small genetic differences among regional subpopulations and among language subgroups. The autosomal allele frequencies can therefore be used for forensics and paternity / kinship testing as a valid nationwide dataset. Additionally, the informative value of the three Y-STR markers included in the PowerPlex ® Fusion 6C kit was assessed. We could demonstrate that the 3-loci-haplotype can be very informative, with an average haplotype frequency in the relevant Western European metapopulation of 0.026.